The Origin of the Welsh Church in Sydney, N.S.W. - Jones, Edward, Mrs. (1901)
From a record of its early activities kept by Mrs Edward Jones of Granville, Sydney, who with her husband was a member of the original group when the church began in February 1901.
Photocopy of typescript.
Manuscript reference no. : NLA MS 3007.
Keywords: Welsh Church (Sydney, N.S.W.)